PENERAPAN FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI TATA HIDANG AMERICAN SERVICE DI SMKN 3 KEDIRI - Brahmana Putra, Dio; Kuncoro Widagdo, Andika; Purwidiani, Niken; Naufal Ahmi, Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the learning outcomes, effectiveness, and influence of implementing lipbook-based learning media on student learning outcomes in the American Service Table Setting course at SMK Negeri 3 Kediri. A quasi-experimental method with a non-equivalent control group design was used, involving an experimental class using flipbook media and a control class using conventional learning. Results showed the experimental class's posttest average (81.57) increased significantly from the pretest (66.14), with a significant Wilcoxon test result (0.000). The N-Gain score of 0.3584 indicated moderate effectiveness, supported by a large effect size (0.72024). The Mann-Whitney U test showed a significant difference between the experimental and control classes.